Foamed neoprene versus thermoplastic elastomer as a wetsuit material: a comparison of skin temperature, biomechanical, and physiological variables - Wiles, T.; Simmons, M.; Gomez, D.; Schubert, M. M.; Newcomer, S. C.; Nessler, J. A. (Sports Engineering, 2022)
Surf wetsuits are made of foamed chloroprene (neoprene), a synthetic rubber that is hard to recycle. Thermoplastic elastomer foam (TPE) may be a more sustainable replacement for neoprene in wetsuit design, but its impact on human thermoregulation and movement has not been evaluated. The purpose of this study was to compare skin temperature, oxygen consumption, heart rate, muscle activation, and arm kinematics while paddling in a thermoplastic elastomer vs. standard neoprene wetsuit. Thirty-three experienced surfers participated in one of two studies: a 60 min simulated surf session in a freshwater swim flume designed to evaluate skin temperature (n = 18), or a dry-land ergometer session designed to evaluate physiological and biomechanical aspects of surfboard paddling (n = 15). Skin temperatures under neoprene were significantly warmer than under thermoplastic elastomer at several anatomical locations including the upper chest (p < 0.01, partial = 0.291), lower abdomen (p < 0.001, partial= 0.527), lower back (p < 0.005, partial = 0.416), lower arm (p < 0.001, partial=0.537), upper leg (p < 0.001, partial= 0.717), and lower leg (p < 0.001, partial= 0.802). However, most participants did not perceive any temperature differences (50%) or felt that the thermoplastic elastomer was warmer (19%). There were no significant differences for any of the other physiological and biomechanical variables analyzed here (p > 0.05). These results suggest that thermoplastic elastomer foam is the less efficient insulator when compared to neoprene, but this difference may be imperceptible to the average surfer. Further, the thermoplastic elastomer wetsuit does not appear to add resistance to or alter upper extremity motion while paddling a dry land ergometer.